KEPATUHAN WAJIB PAJAK BADAN DALAM PERSPEKTIF TAX PROFESSIONAL (Studi Kasus Industri Garment Semarang) - Deviana, Dhisa; Hardiningsih, Pancawati (Proceeding SENDI_U, 2015)
In order to increase revenues in todays world where competition in the form of business intensifies, the governmentneeds to do some efforts and policies in the field of taxation. One cause is not optimal tax revenues caused by thelevel of tax compliance and private entities in paying taxes is still very low. The diversity profile of someone fromdifferences in gender, age, and education level, then weak and pemahamaan knowledge, the financial condition ofthe company, the companys environmental, behavioral control and subjective norms someone who causes thetaxpayer compliance rate in Indonesia is still low in addition to lack of awareness of the taxpayer in paying taxes.Sample in this study was chosen by 73 respondents by using purposive sampling and convenience on taxprofessionals who work in the garment industry in the city of Semarang. Data obtained by distributingquestionnaires. Data analysis was performed using multiple linear regression analysis. The results of this studyindicate that knowledge and understanding of tax laws are significant positive effect on tax compliance agencies,financial condition was not significant positive effect on tax compliance agencies, corporate environment issignificant positive effect on compliance with corporate taxpayers, control the behavior of a significant positiveeffect on tax compliance body, and subjective norm significant positive effect on tax compliance body.Key words : compliance with corporate taxpayers, knowledge and understanding of tax laws, the financialcondition of the company, the company environment, behavioral control and subjective norms.